2013
DOI: 10.3389/fimmu.2013.00233
|View full text |Cite
|
Sign up to set email alerts
|

TNFR2 Expression on CD25hiFOXP3+ T Cells Induced upon TCR Stimulation of CD4 T Cells Identifies Maximal Cytokine-Producing Effectors

Abstract: In this study, we show that CD25hiTNFR2+ cells can be rapidly generated in vitro from circulating CD4 lymphocytes by polyclonal stimuli anti-CD3 in the presence of anti-CD28. The in vitro induced CD25hiTNFR2+ T cells express a conventional regulatory T cells phenotype FOXP3+CTLA4+CD127lo/−, but produce effector and immunoregulatory cytokines including IL-2, IL-10, and IFN-g. These induced CD25hiTNFR2+ T cells do not suppress target cell proliferation, but enhance it instead. Thus the CD25hiTNFR2+ phenotype ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
(36 reference statements)
1
23
0
1
Order By: Relevance
“…It is important to note that our data do not demonstrate a proliferative advantage in TNFR2 hi cells, as a similar proportion of TNFR2 hi and TNFR2 lo cells were BrDU + in both high and low affinity primed groups. This is in line with a previous study that found no difference in proliferation between human CD4 + T cells with high or intermediate levels of TNFR2 expression (11, 13). While we have established a functional role for blocking TNFR2 signals in the context of transplantation, we cannot determine whether this is a CD8 + T cell intrinsic effect or if other cell types are playing a role in these observations.…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that our data do not demonstrate a proliferative advantage in TNFR2 hi cells, as a similar proportion of TNFR2 hi and TNFR2 lo cells were BrDU + in both high and low affinity primed groups. This is in line with a previous study that found no difference in proliferation between human CD4 + T cells with high or intermediate levels of TNFR2 expression (11, 13). While we have established a functional role for blocking TNFR2 signals in the context of transplantation, we cannot determine whether this is a CD8 + T cell intrinsic effect or if other cell types are playing a role in these observations.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, only increases TNFR2 + Tregs (Figure 4 B), but not TNFR2 − Tregs (Figure 4 C) were inversely correlated with effector CD4 T cell function. Given we found ascites also increased TNFR2 + Teffs, and these cells are reported as hyperactive cytokine producers ( 77 ), we tested whether conventional Tregs would be able to suppress their cytokine production. Figure 4 D shows that there was no inverse relationship between conventional Tregs increases and TNFR2 + Teff IFN-γ production, showing they could not suppress this effector T cell subset.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies could also address the influence of IL-6 on different subsets of TNFR2 expressing effector T cells. Previous studies have shown that TNFR2 + effectors were capable upon anti-CD3 and anti-CD28 stimulation of producing a range of cytokines including IFN-y, IL-2 and IL-10 ( 77 , 78 ). It would be particularly interesting to study the effect of IL-6 on cytokine producing Th17 cells given literature suggesting that Th17 plays an important role in the pathogenesis of diverse group of autoimmune diseases as well inflammatory diseases and cancers, including ovarian cancer ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic interventions designed to selectively target ADO and PGE2 pathways could not only inhibit the tumor-derived factors but also silence the suppressive activities of Tregs and thus restore the anti-tumor activity of T effector cells. The last research article shows that a subpopulation of CD25hiTNFR2+ cells generated in vitro from CD4+ cells through TCR stimulation express FOXP3 and other Treg markers, but have effector functions rather than suppressive characteristics ( 21 ).…”
mentioning
confidence: 99%